TIPE VEGETASI HUTAN GAMBUT BEKAS KEBAKARAN DESA KEDATON KABUPATEN OGAN KOMERING ILIR - Dewi Rosanti (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2013)
This paper reports the results of the study of vegetation types on the peat swamp after fireing in the Kedaton Village. Research was conducted between AprilÂ  till Decembre 2013. This research was carried outÂ  using survey method. Sample was taken by purpossive sampling in transect. Data and information gathered included community structure are density, frequency and important value index, selected soil and water quality. Results of the study get 4 types of vegetation growth, are under plants, seedling, sampling and tree. Cyperus rotundus was dominant species on under plant type, Shorea sp was dominant species on seedling type and Dyera lowii was dominant species on sapling and trees type.Key words : peat swamp, vegetation type